2007
DOI: 10.1152/ajplung.00050.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia modulates TGF-β/BMP signaling in a mouse model of bronchopulmonary dysplasia

Abstract: -Prematurely born infants who require oxygen therapy often develop bronchopulmonary dysplasia (BPD), a debilitating disorder characterized by pronounced alveolar hypoplasia. Hyperoxic injury is believed to disrupt critical signaling pathways that direct lung development, causing BPD. We investigated the effects of normobaric hyperoxia on transforming growth factor (TGF)-␤ and bone morphogenetic protein (BMP) signaling in neonatal C57BL/6J mice exposed to 21% or 85% O2 between postnatal days P1 and P28. Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
128
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(137 citation statements)
references
References 58 publications
8
128
1
Order By: Relevance
“…Primary human lung fibroblasts were obtained from Lonza. Primary mouse lung fibroblasts were isolated as described previously (22). The NIH/3T3 mouse fibroblast-like cell line (CRL-1658 TM ) and H441 human Clara cell-like airway epithelial cell line (HTB-174 TM ) were obtained from the American Type Culture Collection.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary human lung fibroblasts were obtained from Lonza. Primary mouse lung fibroblasts were isolated as described previously (22). The NIH/3T3 mouse fibroblast-like cell line (CRL-1658 TM ) and H441 human Clara cell-like airway epithelial cell line (HTB-174 TM ) were obtained from the American Type Culture Collection.…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentration was determined by Bradford assay. Proteins (25 g/lane) were resolved by SDS-PAGE and transferred to nitrocellulose membranes, and immunoblots were probed as described previously (22), using the following antibodies: mouse anti-rabbit Tgfbr3 (Cell Signaling Technology; 2519; 1:1000), mouse anti-rabbit ␤-actin (Cell Signaling Technology; 4967; 1:1000), mouse anti-rabbit phospho-Smad1/5/8 (Cell Signaling Technology; 9511; 1:800), mouse anti-rabbit Smad1 (Cell Signaling Technology; 9743; 1:1000), mouse anti-rabbit phospho-Smad2 (Cell Signaling Technology; 3101; 1:1000), mouse anti-rabbit phospho-Smad3 (Cell Signaling Technology; 9520; 1:1000), mouse anti-mouse Smad2 (Cell Signaling Technology; 3103; 1:1000), mouse anti-rabbit Smad2/3 (Cell Signaling Technology; 3102; 1:1000), rabbit anti-bovine MYH11 (smooth muscle myosin heavy chain 11; Abcam, ab53219; 1:1000), and monoclonal mouse anti-rabbit ACTA2 (␣-smooth muscle actin; Sigma, A-2547; 1:1000). Immune complexes were detected using peroxidase-conjugated secondary antibodies: anti-rabbit (ThermoFisher Scientific; rb:13460; 1:3000) and anti-mouse (ThermoFisher Scientific; ms:31450; 1:3000).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the levels of supplemental oxygen administered to the preterm infant have been substantially reduced in recent years, the levels of oxygen in the bloodstream remain elevated above normal; hence it is important that research is conducted into the effects of hyperoxia on nephrogenesis in the preterm infant. Certainly, experimental studies in the lung have shown that hyperoxia can lead to the generation of oxygen free radicals, infiltration of inflammatory cells, collagen deposition, cellular apoptosis and subsequent tissue injury (McGrath-Morrow and Stahl, 2001;Dieperink et al, 2006;Alejandre-Alcazar et al, 2007;Chen et al, 2007;Chetty et al, 2008). Whether this is also the case in other tissues has not been examined.…”
Section: Factors In the Neonatal Care Of The Infant 421 Hyperoxiamentioning
confidence: 99%